Hubungan Fraksi Kematangan Buah dan Ketinggian Tandan terhadap Jumlah Buah Memberondol pada Panen Kelapa Sawit (Elaeis guineensis Jacq) di Kebun Rambutan PTPN III - Imanjar Ramsanjani Purba; Irsal Irsal; Meiriani Meiriani (Universitas Sumatera Utara, 2017)
ABSTRACT The Relationship between Fraction of Fruit Maturity and Height of Fruit Bunches to the Number of Oil Palm Fruit at Harvesting Oil Palm (Elaeis guineensis Jacq) in Palm Plantation Rambutan PT. Perkebunan Nusantara III. This research was conducted in Palm Plantation Rambutan PT. Perkebunan Nusantara III, Serdang Bedagai District North Sumatra Province from December 2014 until February 2015 using Split Plot Design (SPD) factorial, the main plot is palm bunches height (6, 8 and 10 m) and the subplot is the fraction of oil palm bunches maturity (fraction 1, 2, 3 and 4). The parameters observed were the number of palm fruit that falls from the bunches, free fatty acids and percentages by weight of palm fruit the falls from the bunches with weight of bunches harvested. The results showed that the higher fraction of maturity, significantly increased the number of palm fruit that falls from the bunches, free fatty acids and percentages by weight palm fruit bunches with the fall of the bunches after harvest. The higher harvesting bunches, significantly increased the number of palm fruit that falls from the bunches, free fatty acids and percentages by weight palm fruit bunches with the fall of the bunches after harvest. The interaction between fraction of maturity and height of fruit bunches significantly effected on all parameters observed. Key words : fall from the palm fruit bunches, harvest, palm